1997
DOI: 10.1021/bi962715d
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Protein Kinase C by Coexisting Diacylglycerol-Enriched and Diacylglycerol-Poor Lipid Domains

Abstract: To test the hypothesis that activation of protein kinase C (PKC) is related to the interface between coexisting diacylglycerol- (DAG-) enriched and DAG-poor phases, the thermotropic phase behavior of the ternary mixtures dimyristoylphosphatidylcholine (DMPC)/dimyristoylphosphatidylserine (DMPS)/dioleoylglycerol (DO), DMPC/DMPS/1-palmitoyl-2-oleoylglycerol (PO), and DMPC/DMPS/dimyristoylglycerol (DM) was analyzed and compared with the ability of the lipid mixtures to support PKC activity. Differential scanning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 53 publications
3
42
1
Order By: Relevance
“…However, in the saturated system, activity correlates with 50 -70 mol % DMPC, and in the unsaturated system, with 38 -40 mol % DOPC. These results are suggestive of the involvement of PC in the activating domains, as had been suggested previously with the observation of a DMPC/DMPS/DO fixed ratio compound via Fourier transform infrared spectroscopy (32) and/or with a possible requirement for interface regions between compositionally distinct domains as proposed before (32,33).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…However, in the saturated system, activity correlates with 50 -70 mol % DMPC, and in the unsaturated system, with 38 -40 mol % DOPC. These results are suggestive of the involvement of PC in the activating domains, as had been suggested previously with the observation of a DMPC/DMPS/DO fixed ratio compound via Fourier transform infrared spectroscopy (32) and/or with a possible requirement for interface regions between compositionally distinct domains as proposed before (32,33).…”
Section: Discussionsupporting
confidence: 85%
“…Recent experiments in a DMPC/DMPS/DAG system revealed a peak in PKC activity at DAG mol fractions that corresponded to a mixture of compositionally distinct lipid domains as determined by differential scanning calorimetry (32,33). Potential explanations for the decrease in activity at high mol % DAG included (a) some requirement for interface regions between domains that would be maximal under maximal domain coexistence conditions; (b) a possible dilution of PKC multimers or PKC-substrate aggregates as an optimal domain is increased; and (c) the decrease in mol % PS that would occur as DAG was increased at the expense of PC and PS in those studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In an in vitro system Goldberg et al (57) found that both SAG and sn-1,2-dioleoylglycerol (DO) gave pronounced activation of PKC, which seemed to be related to the increased tendency of SAG and DO to form non-bilayer lipid domains in ternary mixtures of saturated PC and PS (58), whereas other DAGs (dioctanoylglycerol, dipalmitoylglycerol, and oleoyl-acetylglycerol) gave little or no activation. Further studies by these authors (59) showed that SAG and DO also gave conformational changes in the phosphatidylcholine head groups that correlated with the DAG-induced activation of PKC. Studies by others (55,56) with large unilamellar vesicles of saturated PC and PS also indicated that PKC activation may be related to the interphases between DO-rich and DO-poor domains in ternary mixtures with PC and PS.…”
Section: Discussionmentioning
confidence: 92%
“…Lipid lateral domain heterogeneity has been related to PKC activation by DAG (19,42). To investigate the effects of alcohols on the phase behavior of the lipid bilayers, we used DSC and examined the DMPC/DMPS system with octanol and pentanol (Fig.…”
Section: Octanol and Pentanol Change The Phase Behavior And Induce Lamentioning
confidence: 99%